Stemless hemiarthroplasty failure: a challenging revision using reverse total shoulder arthroplasty. Case report and literature review - Cardile, Carlo; Cazzaniga, Carlo; Manzini, Beatrice; Marasco, Roberto; Ragni , Paolo (Acta Biomedica Atenei Parmensis, 2021)
Stemless shoulder prosthesis are used in shoulder arthropathy treatments because of metaphyseal fixation minimizes humeral bone removal, avoids intraoperative and postoperative humeral fracture complications and usually decreases morbidity associated with revision operations. However it’s very important to plan carefully the revision because it could be a high demanding procedure. We report the case of 46 years-old woman with a painful stemless hemiarthroplasty that we revised into a reverse total shoulder arthroplasty. Moreover we describe the possible reasons of this failure and we describe a literature update.